Students' Strategies in Cultivating Their Reading Habit - Hermida, Rita (Lembaga Penelitian, Penerbitan, Pengabdian dan Pengembangan Masyarakat (LP4M) Unmuha, 2021)
This study aims to find out reading strategies used by students at a public university in Aceh in cultivating their reading habit. Data were collected by means of questionnaire and interview. The results showed that most of the students were interested in reading and they had started it before coming to university. Family and friends had a little influence on them as they were self-motivated. The two most common reading habits that they had were having a reading schedule and making a reading list of their favorite book genres. On the other hand, none of them like to either bring books everywhere or read for others. They believed that reading has a lot of benefits, however, they did not want to force others to love reading.